The Influence of Language and Culture on Indonesian Language at ‎SMKN 1 Rancabali‎ - Elina Elina; Aulia Meilani (An International Journal Tourism and Community Review, 2025)
Language is one of the fundamental aspects of human life that functions as a means of communication and cultural identity. In the context of education, the influence of cultural language on the use of Indonesian is an interesting phenomenon to study, especially in the vocational school environment of SMKN 1 Rancabali. This study aims to analyze how cultural language influences the use of Indonesian among students and the implications of this phenomenon are the ability to speak good and correct Indonesian, the research method used is a qualitative approach with interview techniques and direct observation in the field. The results of the study show that students at SMKN 1 Rancabali use regional languages in everyday conversation, especially in informal situations. In an academic context, students tend to switch to Indonesian, although there are still elements of regional languages that are carried over. Awareness of the importance of mastering Indonesian arises when students are in the school environment, such as when interacting in public places.